2008
DOI: 10.1070/qe2008v038n02abeh013599
|View full text |Cite
|
Sign up to set email alerts
|

Study of the optical-discharge plasma in multicomponent mixtures of molecular gases

Abstract: We study path integrals over reparametrizations of the world-sheet boundary. Such integrals arise when string propagates between fixed space-time contours. In gauge/string duality they are needed to describe gauge theory Wilson loops. We show that (1) in AdS/CFT, the integral is well defined and gives a finite 1-loop correction to the Wilson loop; (2) in critical string theory, the integral is UV divergent, and fixed contour amplitudes are off shell. In the second case, we show that the divergences can be remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The continuous optical discharge supported by a CO 2 -laser radiation was extensively studied in the last quarter of last century. At the present time, these studies are continued at the new stage [1] when a possibility was shown of effective synthesis of diamond coating using a continuous optical discharge in the laser plasmatron mode [2]. One of the main characteristic of an optical discharge in this mode is the threshold power of laser radiation that is necessary to maintain the discharge in the dependence on the gas flow rate.…”
Section: Introductionmentioning
confidence: 96%
“…The continuous optical discharge supported by a CO 2 -laser radiation was extensively studied in the last quarter of last century. At the present time, these studies are continued at the new stage [1] when a possibility was shown of effective synthesis of diamond coating using a continuous optical discharge in the laser plasmatron mode [2]. One of the main characteristic of an optical discharge in this mode is the threshold power of laser radiation that is necessary to maintain the discharge in the dependence on the gas flow rate.…”
Section: Introductionmentioning
confidence: 96%